GEOMETRIC RECORDS FROM PARETO PARENTS - López-Blázquez, F; Salamanca-Miño, B (Journal of applied statistical science, 2014)
Geometric records are observations at least λ times larger than all the preceeding observations, being λ > 1 a real number. We study the distribution theory of the geometric records of a sequence of iid observations from a Pareto distribution. Among other results, we obtain representations for the distribution of geometric records, expressions for the density function, and we establish the lognormal limit behaviour of these quantities. We also give some results about the position and number of geometric records.